Increased prevalence of obstructive sleep apnea in patients with pectus excavatum: A pilot study - Yeung-Leung Cheng; I-Shiang Tzeng; Mei-Chen Yang (Tzu-Chi Medical Journal, 2018)
Objective: Laryngomalacia is the most common congenital laryngeal anomaly and is associated with pectus excavatum (PE). Patients with laryngomalacia and patients with obstructive sleep apnea (OSA) both experience upper airway obstruction, and patients with laryngomalacia had been found to have a higher prevalence of PE. However, no studies have established the prevalence of OSA in patients with PE. We conducted this pilot study to evaluate the prevalence of OSA in patients with PE. Materials and Methods: A total of 42 patients ≥20 years old with PE who were admitted for Nuss surgery to correct PE in Taipei Tzu Chi Hospital between October 2015 and September 2016 were invited to participate in the study; 31 of the 42 patients agreed. All 31 patients completed an Epworth sleepiness scale questionnaire to evaluate excessive daytime sleepiness (EDS) and underwent overnight polysomnography to evaluate OSA before Nuss surgery. Results: The prevalence of snoring in the study participants was 100%. Ten of 31 patients (32.3%) reported EDS. The overall prevalence of OSA with an apnea/hypopnea index ≥5/h was 25.8%, and all patients with OSA were men. Conclusions: The prevalence of OSA in patients with PE seemed to be higher than that previously reported in the general population, implying that OSA might be a potential etiology or, at least, an aggravating factor for the development or progression of PE or might be responsible for the postoperative recurrence of PE in some patients. Further studies are needed to clarify this relationship.